Digital currencies in accounting: Evolution and future prospects - Carvalho, D.; Rodrigues, T.; Castro, T.; Penela, D.; Lopes, A. I. (The challenges of era 5.0 in accounting and finance innovation (ICAFI 2024), Conference proceedings, 2024)
This paper articulates an in-depth examination of the evolution and consequential ramifications of digital currencies in the modern financial landscape. It critically explores the historical development of monetary systems, the emergence of digital currencies, their comparative analysis with traditional monetary instruments, and the impacts of blockchain technology in this transition. Employing a systematic literature review, the paper scrutinizes the potential influences of Central Bank Digital Currencies (CBDCs) on enhancing financial inclusivity, security, and operational efficacy. Furthermore, it addresses the multifaceted challenges and prospects digital currencies introduce to the accounting landscape, emphasizing the necessity for a nuanced comprehension of their mechanisms and the broader economic implications thereof.